Using Forest Incomes to Improve Rural Livelihood and Reduce Wealth Inequalities in Nandi County, Kenya - Sumukwo, J. (Africa Environmental Review Journal, 2017)
Non-timber forest products provide a variety of economic benefits to forest-adjacent communities in developing economies. However, the value and significance of forest incomes to rural livelihoods have not been appreciated, as shown in their exclusion from national or/and county income accounting, resulting in incorrect forest management policies and development plans. This paper presents demand-sideanalysis of the contribution of non-timber forest products’ incomes to rural livelihoods in Nandi County, Kenya.Using survey data of 276 households located within a five km radius of Nandi forest, the study examined household income diversification strategies and the income equalizing effects of forest income by applying inverse Simpson index of diversity and Gini coefficient computations, respectively. Results show that forest-fringe households used off-farm and portfolio of forest activities for income diversification. The non-timber forest income had a strong equalizing effect (Gini reduction of 9%), contributing 26% of the household income (average of Ksh. 68,261 per annum) while farm and off-farm incomes contributedSh.139,147 (53%) and Sh. 55,134 (21%), respectively. Restricting access of the rural poor to non-timber forest products would lead to increased income inequalities with substantial loss to households’ welfare. The study recommended that forest management programs, which enhance supply of forest economic benefits to adjacent communities, be an integral component of conservation efforts.